Structures in law: A new way to reconstruct law using logical tools from philosophy of science. - Meier, Pascal Felix (Synthese, 2025)
Philosophy of science offers as yet untapped potential to inform legal theory. This paper explores some of it. Drawing on and adapting logical tools from the semantic and structuralist views of scientific theories, I propose a formal framework for analysing legal norms. I illustrate how it works by applying it to a simple yet realistic tort case pursuant to Swiss law. The formalism allows reconstructing the subsumption of a case under a norm as isomorphic embedding. Legal norms and connections between them are captured using functions. The reconstruction helps clarify some questions about interpreting and applying legal rules, their interactions in legal systems, the phenomenon of normativity, what a court should say to justify its verdicts, and connects to contemporary metaethics since the resulting formalism suggests a feasible method to write out the Ramsey-sentence which Jackson-style moral functionalism promises. By representing legal doctrine using meta-theoretical methods apt to represent scientific theories, the study also contributes to locating jurisprudence in the universe of rational enquiry as at least in some ways on a par with science.